Enhancing Elementary Students’ Mathematical Problem-Solving Skills through Fraction Board Manipulatives Media - Dewi Anggraeni; Linda Astriani (Edumatika, 2026)
Background: Many elementary school students experience difficulties in solving word problems on fractions due to limited conceptual understanding and challenges in performing fraction operations. Purpose: This study examined the effect of fraction board media on fourth-grade students’ mathematical problem-solving skills in fraction tasks. Method: A quantitative approach with a quasi-experimental posttest-only control group design was employed. The sample consisted of 56 fourth-grade students in South Jakarta, divided equally into experimental and control group. Data were collected using five items of essay test based on Polya’s problem-solving indicators (reliability coefficient = 0.809) and analyzed using an independent sample t-tests. Findings: The result showed a significant difference between the two groups (t = 9.263, p = 0.000). Students who learn using fraction board media demonstrated higher mathematical problem-solving skills than those who received conventional instruction. Implications: Fraction board media can serve as a low-cost and effective instructional tool for elementary teachers to support students’ conceptual understanding and enhancing problem-solving skills in fraction learning. Originality: This study provides empirical evidence of the effectiveness of fraction board media in improving fourth-grade students’ mathematical problem-solving skills on fraction topics through a quasi-experimental approach.